Webster's School thesaurus. (Springfield, Mass. G. & C. Merriam, 1980)
Includes more than 43,000 synonyms, antonyms, and contrasted and related words.
Published in 1978 under title: Webster's students thesaurus.
Keywords: English language -- Synonyms and antonyms; English language -- Synonyms and antonyms